Complementariedade do processo inovativo no Brasil: a decisão de produzir ou comprar inovação - Aguiar, Fernando Amaral de (2018)
Studies on the impact of technological innovation on the economy have spread through the literature. A specific field seeks to understand the advantages that a company or an industry has in deciding to produce technology internally or to buy it from third parties and to apply to existing processes. This paper reproduces the study by Cassiman and Veugelers (2006) and questions whether there is complementarity in the innovative process of the transformation industry in Brazil. The goal is to understand if the results found by the Belgian authors would be similar or different to Brazil, given the peculiarities of the Brazilian innovation sector. The evidence suggests that it is more advantageous for the transformation industry to buy technology rather than to invest in the creation of innovations within the sector. Therefore, the innovative process lacks complementarity. A possible explanation for this finding regards some particularities of Brazil, such as low labor productivity, excessive bureaucracy, low protection of intellectual property, but further investigation is necessary to distinguish the effects of those variables. This work is a pioneer in this topic for Brazil, and, for such reason, it does not exhaust the possibilities of inclusion of variables in the proposed models. The goal here is to introduce the subject and to raise discussions.